2018
DOI: 10.1111/avsc.12403
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of β‐diversity: Evidence from plant communities in a semi‐natural system

Abstract: Question: Do remote sensing signals represent β-diversity? Does β-diversity agree with community types? Location: UNESCO Man and the Biosphere Reserve, La Palma, Canary Islands. Methods: We recorded perennial, vascular plant species abundances in 69 plots (10 m × 10 m) in three pre-defined community types along an elevational gradient of 2,400 m: succulent scrubland, Pinus canariensis forest and sub alpine scrubland. The remote sensing data consists of structural variables from airborne Light Detection and Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 86 publications
3
25
0
Order By: Relevance
“…The relationship between γ-diversity and elevation was negative for all life forms as has been previously reported for other regions and type of ecosystems [23,38,68]. The lower species richness observed at higher elevational zones may be partly due to the area effect, as area decreases with increasing elevation due to conical shape of mountains [69], and therefore according to species-area relationship, the species richness also decreases [22].…”
Section: Discussionsupporting
confidence: 69%
“…The relationship between γ-diversity and elevation was negative for all life forms as has been previously reported for other regions and type of ecosystems [23,38,68]. The lower species richness observed at higher elevational zones may be partly due to the area effect, as area decreases with increasing elevation due to conical shape of mountains [69], and therefore according to species-area relationship, the species richness also decreases [22].…”
Section: Discussionsupporting
confidence: 69%
“…Lotus campylocladus subsp. hillebrandii , Cistus symphytifolius or Adenocarpus foliolosus ; Hoffmann et al., ). With time, the influence of the surrounding (mature) communities likely becomes increasingly important as propagule sources for the lava flows, often leading to successional trajectories converging towards the surrounding communities (Prach et al., ; Rolim, Machado, & Pillar, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a survey on La Palma island, Canary islands, Hoffmann et al. () investigated whether beta‐diversity patterns agree with community types and if remotely sensed data can be used to detect compositional changes of elevational belts. They found that at the lower ecotone, i.e.…”
Section: Statistical Approaches To Identify Vegetational Belts Based mentioning
confidence: 99%